2006
DOI: 10.1152/ajplung.00158.2005
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling controls PASMC KV channel expression in vitro and in vivo

Abstract: Bone morphogenetic proteins (BMPs) have been implicated in the pathogenesis of familial pulmonary arterial hypertension. The type 2 receptor (BMPR2) is required for recognition of all BMPs. Transgenic mice with a smooth muscle cell-targeted mutation in this receptor (SM22-tet-BMPR2 delx4ϩ ) developed increased pulmonary artery pressure, associated with a modest increase in arterial muscularization, after 8 wk of transgene activation (West ). In the present study, we show that these transgenic mice developed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…Consistently, transgenic mice expressing a dominant-negative Bmpr2 gene in smooth muscle cells (SM22-tet-BMPR2delx4+) develop increased pulmonary arterial pressure, associated with a modest increase in arterial muscularisation [47]. To test whether anomalies seen in SM22-tet-BMPR2delx4+ are mediated by reduced K V channel expression, YOUNG et al [48] investigated the expression levels of several K V channels and revealed a pronounced diminution of K V 1.5 protein expression in the lungs of transgenic mice. Consistent with this, treatment of PASMCs with recombinant BMP2 stimulates K V 1.5 expression and was accompanied by increased current density in these cells; a functional effect blocked by an anti-K V 1.5 antibody [48,49].…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, transgenic mice expressing a dominant-negative Bmpr2 gene in smooth muscle cells (SM22-tet-BMPR2delx4+) develop increased pulmonary arterial pressure, associated with a modest increase in arterial muscularisation [47]. To test whether anomalies seen in SM22-tet-BMPR2delx4+ are mediated by reduced K V channel expression, YOUNG et al [48] investigated the expression levels of several K V channels and revealed a pronounced diminution of K V 1.5 protein expression in the lungs of transgenic mice. Consistent with this, treatment of PASMCs with recombinant BMP2 stimulates K V 1.5 expression and was accompanied by increased current density in these cells; a functional effect blocked by an anti-K V 1.5 antibody [48,49].…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Cmentioning
confidence: 99%
“…To test whether anomalies seen in SM22-tet-BMPR2delx4+ are mediated by reduced K V channel expression, YOUNG et al [48] investigated the expression levels of several K V channels and revealed a pronounced diminution of K V 1.5 protein expression in the lungs of transgenic mice. Consistent with this, treatment of PASMCs with recombinant BMP2 stimulates K V 1.5 expression and was accompanied by increased current density in these cells; a functional effect blocked by an anti-K V 1.5 antibody [48,49]. The mechanism of K V 1.5 regulation by BMP signalling is unclear.…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Cmentioning
confidence: 99%
“…Low levels of Kv1.5 gene expression and channel activity are hallmarks of human and experimental PH, including the chronic-hypoxia and monocrotaline models (Yuan et al, 1998a;Yuan et al, 1998b;Reeve et al, 2001;McMurtry et al, 2004;McMurtry et al, 2005;Bonnet et al, 2006;Guignabert et al, 2006;Young et al, 2006;Remillard et al, 2007;Archer et al, 2008;Guignabert et al, 2009). However, the underlying mechanism of Kv1.5 in PH (Yu et al, 2001), a signal-transducing transcription factor of the AP-1 family, and nuclear factor of activated T cells (NFAT) (Remillard et al, 2007).…”
Section: Expression and Activity Of The Kv15 Channel In The Pathogenmentioning
confidence: 99%
“…[Ca 2+ ]i is determined in part by the influx of Ca 2+ through voltage-gated, L-type Ca 2+ channels, 5,6) which are gated based on the membrane potential (Em) of the SMCs. 3,7) In pulmonary arterial smooth muscle cells (PASMCs), the Em is partially regulated by voltagegate K + (Kv) channels, and blocking Kv channels causes increased [Ca 2+ ]i. 3,[7][8][9] Each Kv is composed of both pore-forming α-and β-subunits.…”
Section: Introductionmentioning
confidence: 99%
“…3,7) In pulmonary arterial smooth muscle cells (PASMCs), the Em is partially regulated by voltagegate K + (Kv) channels, and blocking Kv channels causes increased [Ca 2+ ]i. 3,[7][8][9] Each Kv is composed of both pore-forming α-and β-subunits. The Kv α-subunits, including Kv1.2, Kv1.5, Kv2.1, and Kv9.3, are O 2 -sensitive channels and are expressed in PASMCs.…”
Section: Introductionmentioning
confidence: 99%